2009
DOI: 10.1002/jor.20932
|View full text |Cite
|
Sign up to set email alerts
|

TRITON‐X is most effective among three decellularization agents for ACL tissue engineering

Abstract: Ruptures of the anterior cruciate ligament (ACL) are still associated with high rates of long-term complications, even in patients undergoing modern, state-of-the-art replacement. Tissue-engineering approaches have been shown to be of value in improving treatment of ACL ruptures. However, the success of tissue-engineering procedures depends on the choice of an appropriate biomaterial. Decellularized ACL tissue potentially combines the structural composition of the targeted tissue with a reduced risk of graft r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 47 publications
4
92
0
1
Order By: Relevance
“…This suggests that the sulfated GAG removal during the decellularization process is influenced not only by the type of detergent used but also by the swelling of the tissue induced by additional alkaline treatment. In agreement with our observation, Vavken et al reported a lower reduction of GAG content in porcine anterior cruciate ligament tissue after decellularization with TX100 compared to trypsin and sodium dodecyl sulfate [37].…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the sulfated GAG removal during the decellularization process is influenced not only by the type of detergent used but also by the swelling of the tissue induced by additional alkaline treatment. In agreement with our observation, Vavken et al reported a lower reduction of GAG content in porcine anterior cruciate ligament tissue after decellularization with TX100 compared to trypsin and sodium dodecyl sulfate [37].…”
Section: Discussionsupporting
confidence: 93%
“…[15][16][17][18][19][20][21] Results obtained after applying different detergent-based protocols remain conflicting. While t-octyl-phenoxypolyethoxyethanol (Triton X-100) did not lead to satisfactory results in an early study, 15 it was found to be most effective by others.…”
Section: Introductionmentioning
confidence: 99%
“…While t-octyl-phenoxypolyethoxyethanol (Triton X-100) did not lead to satisfactory results in an early study, 15 it was found to be most effective by others. 19 Sodium dodecyl sulfate (SDS) was reported to be effective but to reduce cytocompatibility due to matrix alterations; however, the protocol used in these studies did not only include incubation in SDS, but also in Triton X-100. 11,17,22,23 Further, several groups performed detergent-based decellularization with samples that had previously been frozen or freezedried 15,16,24 ; it should be acknowledged that this may have had an additional effect on decellularization effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Triton x100 is less harmful to glycosaminoglycans when compared to the other decellularization agents 26,27 . In our experiments, the apparent destruction of the remaining extracellular matrix seen at Figure 4 (C,E,F) are not due to the detergent exposure, but a histological processing artifact.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the first set of protocols, our findings does not corroborate with Elder et al 13 when they describe the action of the SDS and Triton x100 detergents as an effective process of decellularizing articular cartilage 13 with complete lyses of It was previously reported that the employment of SDS causes some destruction of the cartilage tissue, due to the fact that SDS is an ionic detergent, which is efficient in the solubilization of cytoplasmatic and nuclear cell membranes, tends to denature protein by disrupting the protein-protein interactions, can remove glycosaminoglycans content, and collagen 11,26 . The nonionic detergents, like triton x100, act more mildly on the tissue structures and have the disruption of lipidlipid and lipid-protein interactions as a mechanism of action 11 .…”
Section: Discussionmentioning
confidence: 99%